2018
DOI: 10.1007/s11663-018-1371-z
|View full text |Cite
|
Sign up to set email alerts
|

Yttria-Stabilized Zirconia Aided Electrochemical Investigation on Ferric Ions in Mixed Molten Calcium and Sodium Chlorides

Abstract: Electrolytic reduction of dissolved iron oxide to metal iron in molten salts with an inert anode is an alternative short route for steelmaking without CO2 emissions. A novel and simple integrated yttria-stabilized zirconia (YSZ) cell was constructed from a YSZ tube with a closed end. The YSZ tube played multiple functions, including the container for the molten salts, the solid electrolyte membrane in the O 2-| YSZ | Pt | O2 (air) reference electrode (RE), and the solid electrolyte membrane between the working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The leaching solution of zinc suboxide was tested with square wave voltammetry at different frequencies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in the potential range of −1.2 V to 0 V. The results are shown in Figure 4a. It can be seen from the Figure that there are two peaks (B′, C′) in the potential range of −1 V to −0.6 V, and peak B′ corresponds to the reduction process of cadmium.…”
Section: Square Wave Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The leaching solution of zinc suboxide was tested with square wave voltammetry at different frequencies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in the potential range of −1.2 V to 0 V. The results are shown in Figure 4a. It can be seen from the Figure that there are two peaks (B′, C′) in the potential range of −1 V to −0.6 V, and peak B′ corresponds to the reduction process of cadmium.…”
Section: Square Wave Voltammetrymentioning
confidence: 99%
“…It can be observed that the measured Iτ 1/2 has nothing to do with I and closely matches the horizontal straight line within the required accuracy. Therefore, it can be determined that the reduction in this step is a diffusion control process in solution [17].…”
Section: Chronopotentialmentioning
confidence: 99%
“…In order to reduce the error, the origin and experimental data points were put together to fit a straight line. Some researchers had also adopted this method [24][25][26].…”
Section: Square Wave Voltammetry and Open Circuit Potentialmentioning
confidence: 99%
“…After the YSZ tube was ultrasonically cleaned with alcohol, the porous annular Pt CE (area about 6.28 cm 2 ) and RE (area about 1.88 cm 2 ) were prepared according to the method provided in literature. [26,28] The Pt leads (diameter 0.5 mm and length 800 mm) for the RE and the CE were each protected in a thin double-bore alumina tube.…”
Section: B Integrated Cell and Electrodesmentioning
confidence: 99%
“…After holding the temperature, a Ni wire (purity 99.99%, diameter 0.5 mm) was used as cathode to pre-electrolyze for 90 min at -1.8 V. After the Ni wire was removed, the Mo-SiO2 WE was slowly lowered from the furnace top to the above of the melt level, and then the melt level was determined by the open circuit potential method to ensure that the whole SiO2 cylinder was immersed in the melt. [28] Electrochemical behavior of the Mo-SiO2 WE was investigated by cyclic voltammetry (CV) method. Based on this test, the electroreduction of solid SiO2 was studied at a lower overpotential by chronoamperometry (potentiostatic electrolysis) method.…”
Section: B Integrated Cell and Electrodesmentioning
confidence: 99%